IDENTIFICATION OF CASSAVA CRACKERS LONG TERM AGROINDUSTRIAL RELATIONSHIP PATTERN AND ANALYSIS OF SUPPLY CHAIN EXISTENCE - Rini Dwi Astuti; Tatiek Koerniawati Andajani (UPT Penerbitan Universitas Jember, 2012)
Cassava is always been economically valuable agriculture commodity since it can be produced into a lot of agroindustry product such as cassava crackers. In order to survivein competing business circumstance, cassava crackers producers should produce better,cheaper and faster product. This research is aimed to study the contractual relationshippattern which can be categorized into five dimension satisfaction, trust, communication,mutual interdependency and commitment. Research finding states that although there was a long term relationship among agents, yet there wasn’t any supply chain.